Caracterização física, físico-química e química das águas do rio Guamá (rio Aurá) e o entendimento do efeito causado pela ocupação humana no ambiente aquático - (:unkn) unknown (Museu Paraense Emílio Goeldi, 1998)
The city of Belém is cutted and limited by rivers, lakes, streams and bays that suffer the action of human occupation. The characterization of the rivers Guamá and Aurá is, with the advance of the studies of the project AQUALIVITA, giving subsidies to evaluate the degree of pollution in these bodies of water and the contribution of this pollution in the degradation of the aquatic environment, especially because the leachate produced by the Aurá Landfill is not properly controlled and reaches the streams Santana and Jaruca, and the rivers Aurá and Rio Guamá, causing changes that are monitored as the object of this research. The parameters analyzed are pH, temperature, electrical conductivity and dissolved oxygen. Four collections were made alternating between dry and rainy seasons, at high and low tide. The dissolved oxygen in natural waters has values around 8 mg/l, and in the Amazon these values are around 7 mg/1. With the analyses performed we found in some points of the Aurá River, values around 3 mg/l of O.D., which is limiting for aquatic life. The electrical conductivity, a parameter that measures the content of dissolved substances in water, was many times higher than the natural conductivity of the region (measured at points where the slurry does not reach), which is around 25. It can be concluded that the waters of the Aurá River and its tributaries that receive the slurry after passing through the stabilization pond are undergoing important transformations in the vicinity of the dump. This influence is minimized on the way to Rio Guamá, due to several factors, such as dilution, sedimentation, reoxygenation, degradation, release of gases, etc. The ecological damage was observed through the death of fish in the Aurá River, which alarms the riverside population, because the cause seems to be the contamination of the water, but, in reality, it is the lack of oxygen. A proper monitoring and measures in the slurry stabilization system can control this situation.
Physical, physicochemical and chemical characterization of the waters of the Guamá (Aurá) river and the understanding of the effect caused by human occupation on the aquatic environment
Keywords: Água; Rio Guamá; Rio Acará; CNPQ::CIENCIAS BIOLOGICAS::ECOLOGIA